DustCube, a nanosatellite mission to binary asteroid 65803 Didymos as part of the ESA AIM mission. Issue 12 (15th December 2018) - Perez, Franco; Modenini, Dario; Vázquez, Antonio; Aguado, Fernando; Tubío, Ricardo; Dolgos, Gergely; Tortora, Paolo; Gonzalez, Alberto; Lasagni Manghi, Riccardo; Zannoni, Marco; Nazeeruddin, Adeeb; Melozzi, Mauro; et al.
Abstract: Nanosatellites are a promising option for the exploration of the solar system and near-Earth objects, providing an agile, reduced cost and mass solution for interplanetary missions. This paper summarises the efforts done during the Phase A study aimed at assessing the feasibility of a nanosatellite-based mission concept for a 3U CubeSat to the vicinity of the binary asteroid 65803 Didymos. The nanosatellite is meant to be part of the Asteroid Impact Mission (AIM) which is the European element of the NASA-ESA jointly developed Asteroid Impact & Deflection Assessment (AIDA) mission. The inclusion of a scientific optical payload based on a Nephelometer, the selected orbital and navigation strategy, together with the differences found between the Beyond-Earth space environments (radiation, micrometeoroids, ejected material, illumination conditions, communications access) and a typical LEO polar environment, unveils new technical challenges to be faced along interplanetary missions. These challenges have been identified and analysed to be included within the DustCube concept of operations, are described in this manuscript.